SYSTEMATIC LITERATURE REVIEW: PENGARUH PENERAPAN ARTIFICIAL INTELLIGENCE TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Luthfi Anugrah Pribadi; Totok Dewayanto (Diponegoro Journal of Accounting, 2025)
This study aims to identify the relationship between Artificial Intelligence (AI) and Accounting Information System (AIS) based on published research articles. This study also aims to examine the diversity of results and patterns in terms of recommendations and contributions. Then, this study also explores gaps in science to develop future academic studies.This study uses a systematic literature review (SLR) method to analyze various articles published in academic journals indexed in the SCImago Journal Rank (SJR) published from 2018 to 2025, which focus on articles conducted in the Asia Pacific (APAC) and Europe-Middle East-Africa (EMEA). Articles are filtered using defined keywords obtained from various top ranking journals. The SLR method is used to examine topics/themes, results, methodologies, recommendations, and limitations of published articles.The results of the analysis provide evidence that academic studies prove the importance of Artificial Intelligence in Accounting Information System are related to technology selection, pressure from government regulations and competitors, and human resource considerations. Most companies define Accounting Information System (AIS) in the form of enterprise resource planning (ERP), therefore ERP development always has appeal and becomes the focus of subsequent research. In terms of number, articles published in the APAC region dominate compared to EMEA, meaning that there is a positive development in the application of AI and academic studies of AIS in the Asia Pacific region. It was also found that the implementation of AI had a positive impact on companies in various sectors and company scales. This finding is expected to provide substantial benefits to accounting information, developers in terms of AI development in organizations and recommends exploring AIS more about the environmental impact of using technology.